Clinical features of dental status of patients with eating disorders. The relationship of pathologies of the oral mucosa and gastrointestinal tract (Эндодонтия Today)
The article presents an overview of the literature on the problem of combining lesions of the oral mucosa of patients with diagnoses of eating disorders and chronic diseases of the digestive system as related. The features of the influence of somatic pathology on the nature and severity of pathological processes in the oral cavity. People suffering from bulimia and anorexia are at risk for dental disease. Analyzing the cause and effect of diseases of the mouth and gastrointestinal tract, most authors have found that the pathology of the digestive system often precedes the appearance of dental diseases. Identified oral lesions have a clear correlation with the degree of damage to internal organs.